Lentiviral-mediated expression of cytochrome P450 2D6 in HepaRG cells: new means for in vitro xenobiotic biotransformation and cellular response to chimeric viral mRNA - Hugo Coppens-Exandier; Franz Mackanga; Thomas Darde; Corentin Bonhomme; Gaëlle Angenard; Patricia Leroyer; Catherine Ribault; Thomas Gicquel; Romain Pelletier; Flyuza Roshchina; Estelle Schaefer; Christophe Chesné; et al. (Archives of Toxicology, 2026)

Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Post-plasma catalysis for toluene abatement using Mn, Cu, and MnCu oxide on a hydroxyapatite support - Anastasiia Gromova; Jean-Marc Giraudon; Karen Leus; Maryam Nilkar; Mikhail Gromov; Pascal Van Der Voort; Christophe Leys; Jean-François Lamonier; Nathalie De Geyter; Rino Morent (Journal of Environmental Chemical Engineering, 2026)

Multi-scale Study of the Effect of a Living Yeast-Based Biostimulant on Soybean - Marie Chambard; Anouk Lyver; Mohamed Amine Ben Mlouka; Benjamin Albert; Camille Profizi; Elodie Cusset; Jean-Christophe Avice; Pascal Cosette; Isabelle Trinsoutrot-Gattin; Isabelle Boulogne; Mélanie Bressan (Journal of Plant Growth Regulation, 2026)

Expanding the application of the TAIL rating scheme to schools: schoolTAIL - Minh Tien Tran; Wenjuan Wei; Claire Dassonville; Christophe Martinsons; Pascal Ducruet; Mickaël Derbez; Corinne Mandin; Valérie Héquet; Pawel Wargocki (Energy and Buildings, 2026)

Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Giant clam gardens: Cultural practices and ecological implications for population resilience in New Caledonia - Pascal Dumas; Cecile Portes; Christophe Peignon (Ocean & Coastal Management, 2026)

The role of barrier reef protection to storm surge during tropical cyclones in a narrow lagoon, New Caledonia, south west Pacific - Maxime Duphil; Jérôme Lefèvre; Swen Jullien; Jean Roger; Pascal Dumas; Romain Le Gendre; Jérôme Aucan; Myriam Vendé-Leclerc; Martin Bénébig; Christophe Menkes (Continental Shelf Research, 2025)

Early stages impact of volcanism on sedimentary diagenesis: The case of the newly born volcano, Fani Maoré - Marine Manoux; Christophe Rabouille; Jean-Pascal Dumoulin; Bruno Bombled; Gaël Monvoisin; Sandrine Cheron; Audrey Boissier; Yoan Germain; Lucie Pastor; Olivier Rouxel; Cécile Cathalot (Chemical Geology, 2025)

Tectono-sedimentary evolution of the Southern Atlas front of Tunisia using integrated subsurface data: A case study of the Gantass structure - Dalel Manai; Mohamed Hedi Inoubli; Christophe Pascal; Marwa Ghalgaoui; Kawthar Sebei; Adnen Amiri; Ali Mahroug (Journal of Mountain Science, 2025)

Multifactored accelerated marine corrosion of immersed steels influenced by washed ashore Sargassum rafts - Diana Bénuffé; Fatima Radouani; Maxence Quemener; Olivia Ozier; Marilyne Fauchon; Yannick Toueix; Fabienne Faӱ; Anthony Magueresse; Benoit Lescop; Stéphane Rioual; Pascal Zongo; Christophe Roos; et al. (Marine Environmental Research, 2025)

Modeling the impact of natural roughness of tension joints on heat transport - Benoit Nigon; Christophe Pascal; Andreas Englert (Geothermics, 2024)

Intensification of ex-situ biomethanation in a bubble column bioreactor by addition of colonized biochips - Misagh Keramati; Kadir Erdogan; Jean-Sébastien Guez; Alina Violeta Ursu; Pascal Dubessay; Christophe Vial; Pierre Fontanille (Bioresource Technology Reports, 2024)

Comparison of methane yield of a novel strain of Methanothermobacter marburgensis in pure and mixed adapted culture derived from a methanation bubble column bioreactor - Corinne Biderre-Petit; Mariem Mbarki; Damien Courtine; Yanis Benarab; Christophe Vial; Pierre Fontanille; Pascal Dubessay; Misagh Keramati; Isabelle Jouan-Dufournel; Arthur Monjot; Jean Sébastien Guez; Khaled Fadhlaoui (Bioresource Technology, 2024)

Farming activity and risk of treated thyroid disorders: Insights from the TRACTOR project, a nationwide cohort study - Pascal Petit; Sylvain Chamot; Abdallah Al-Salameh; Christophe Cancé; Rachel Desailloud; Vincent Bonneterre (Environmental Research, 2024)

Effect of an organophosphorus insecticide, soil texture and earthworm species on the turnover of soil, gut and cast microbiota during the earthworm's gut transit - Pascal Mirleau; Fatina Jouni; Juliette Chappat; Christophe Mazzia; Juan Carlos Sanchez-Hernandez; Yvan Capowiez; Magali Rault (Soil Biology and Biochemistry, 2024)

Photodegradation of disposable polypropylene face masks: Physicochemical properties of debris and implications for the toxicity of mask-carried river biofilms - Isabelle Bihannic; Renaud Gley; Lucas Gallo; Apolline Badura; Angelina Razafitianamaharavo; Maximilien Beuret; David Billet; Clément Bojic; Céline Caillet; Philippine Morlot; Marie Zaffino; Fatina Jouni; et al. (Journal of Hazardous Materials, 2024)

Hydrogen and Fatty Acid Production by Dark Fermentation of Sweet Sorghum Stalks as an Efficient Pre-treatment for Energy Recovery Before Their Bioconversion into Methane - Bakari Hamadou; Djomdi Djomdi; Ruben Zieba Falama; Christine Gardarin; Christelle Blavignac; Fabrice Audonnet; Cedric Delattre; Guillaume Pierre; Pascal Dubessay; Roger Djouldé Darnan; Philippe Michaud; Gwendoline Christophe (BioEnergy Research, 2024)

Low concentrations of ethylene bisdithiocarbamate pesticides maneb and mancozeb impair manganese and zinc homeostasis to induce oxidative stress and caspase-dependent apoptosis in human hepatocytes - Kilian Petitjean; Yann Verres; Sébastien Bristeau; Catherine Ribault; Caroline Aninat; Christophe Olivier; Patricia Leroyer; Martine Ropert; Olivier Loréal; Olivier Herault; Laurence Amalric; Nicole Baran; et al. (Chemosphere, 2024)

Does prenatal exposure to multiple airborne and tap-water pollutants increase neonatal thyroid-stimulating hormone concentrations? Data from the Picardy region, France - Sylvain Chamot; Abdallah Al-Salameh; Pascal Petit; Vincent Bonneterre; Christophe Cancé; Guillaume Decocq; Agnès Boullier; Karine Braun; Rachel Desailloud (Science of The Total Environment, 2023)

Binders in foods: Definition, functionality, and characterization - Eva Herz; Pascal Moll; Christophe Schmitt; J. Weiss (Food Hydrocolloids, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Heat flow of northern Norway, new data and geodynamic implications - Christophe Pascal; Niels Balling (Tectonophysics, 2023)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

Root‐released organic compounds in aquaponics and their potential effects on system performance - Paula Senff; Björn Baßmann; Frederik Kaiser; Harvey Harbach; Christophe Robin; Pascal Fontaine (Reviews in Aquaculture, 2023)
Optimizing production in aquaponics requires in‐depth knowledge of the plant, fish and microbial compartments. This opinion paper is focused on root‐released organic compounds and their implication in aquaponics, an area that has received little to no direct research to date. Key scientific literature from two distinct fields of study—phytochemicals in aquaculture science and root exudates in plant science—reveals possible pathways and effects. Root exudates, passively or actively released by plants as a stress response, protection or signalling, have the potential to influence the systems microbiome and the cultured fish, as similar phytochemicals have been found to affect bacterial abundance and diversity and fish health and behaviour. These are key aspects to run aquaponics successfully, which shows the need for further investigation to better understand sources and mechanisms of such molecules and possible ways to harness beneficial effects that can guide new research directions as the role of aquaponics grows in recirculating aquaculture.

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

The subsurface thermal state of Svalbard and implications for geothermal potential - Kim Senger; Matthijs Nuus; Niels Balling; Peter Betlem; Tom Birchall; Hanne H. Christiansen; Harald Elvebakk; Sven Fuchs; Malte Jochmann; Peter Klitzke; Kirsti Midttømme; Snorre Olaussen; et al. (Geothermics, 2023)

Offshore-onshore tectonomagmatic correlations: Towards a Late Mesozoic non-Andean-type Cathaysian continental margin - Changhai Xu; Yuling Deng; Calvin G. Barnes; Hesheng Shi; Christophe Pascal; Yuanyuan Li; Shunli Gao; Donghui Jiang; Jianlei Xie; Changqian Ma (Earth-Science Reviews, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Homogenization increases stickiness of concentrated pea protein - apple pectin mixtures - Pascal Moll; Hanna Salminen; Miriam Spengler; Christophe Schmitt; Jochen Weiss (Journal of Food Engineering, 2023)

Bubble functionalization in flotation process improve microalgae harvesting - Irem Demir-Yilmaz; Malak Souad Ftouhi; Stéphane Balayssac; Pascal Guiraud; Christophe Coudret; Cécile Formosa-Dague (Chemical Engineering Journal, 2023)

Analog experiments in volcanology: towards multimethod, upscaled, and integrated models - Sam Poppe; Johan T. Gilchrist; Eric Christophe Pascal Breard; Alison Graettinger; Stephen Pansino (Bulletin of Volcanology, 2022)

Fishing behaviours and fisher effect in decision‐making processes when facing depredation by marine predators - Anaïs Janc; Christophe Guinet; David Pinaud; Gaëtan Richard; Pascal Monestiez; Paul Tixier (Fisheries Management and Ecology, 2021)
Fishers aim to optimise cost–benefit ratios of their behaviour when exploiting resources. Avoidance of interactions with marine predators (i.e. their feeding on catches in fishing gear, known as depredation) has recently become an important component of their decisions. How fishers minimise these interactions whilst maximising fishing success is poorly understood. This issue is addressed in a sub‐Antarctic, long‐line fishery confronted with extensive depredation by sperm whales Physeter macrocephalu s and killer whales Orcinus orca by examining a 15‐year data set. Whereas a broad range of behaviours was identified from spatio‐temporal and operational descriptors, none combined high fishing success with low frequency of interactions. With experience, fishers favoured exploitation of productive patches with high frequencies of interactions over avoidance behaviours. Such decisions, although potentially optimal in the short term, are likely to intensify pressures on fish stocks and impact depredating whales. Therefore, the present study provides additional evidence to inform management decisions pertaining to the coexistence between fisheries and marine predators.

Commensal small mammal trapping data in Southern Senegal, 2012–2015: where invasive species meet native ones - Laurent Granjon; Odile Fossati‐Gaschignard; Emmanuelle Artige; Khalilou Bâ; Carine Brouat; Ambroise Dalecky; Christophe Diagne; Mamoudou Diallo; Philippe Gauthier; Pascal Handschumacher; Mamadou Kane; Lætitia Husse; et al. (Ecology, 2021)
Describing patterns and testing hypotheses on processes driving biological invasions represent major issues in ecology. Addressing these questions requires building adequate data sets, i.e., covering areas and spanning periods adapted to the invasion processes studied. Rodents include major invasive species, among which the black rat Rattus rattus and the domestic mouse Mus musculus have nearly colonized the entire world, from their native Asian range. To do so, they have benefitted from their ability to cope with human‐modified environments and to live in the immediate vicinity of Man, who served as a vector of their dispersal between regions and continents. In Senegal, both R . rattus and M . musculus , initially introduced by early West European colonizers some centuries ago, are currently expanding thanks to road traffic and infrastructure development and rampant urbanization that concerns even remote regions of the country. As part of projects aimed at studying (1) the role of invasive black rat populations in the emergence of zoonotic diseases in southeastern Senegal, and (2) the evolutionary consequences of parasites in R . rattus and M . musculus invasions in Senegal, we conducted a series of field campaigns throughout the southern half of the country, between May 2012 and September 2015. The objectives were to catch commensal small mammals using standard trapping procedures, identify them using morphological or molecular tools, and take samples from them upon autopsy, to look for zoonotic parasites and pathogens. Along with data on individual specimens, information on microhabitats was gathered at each trap position. This resulted in the constitution of a data set of more than 13,000 trapnights, which allowed the capture of more than 3,100 small mammals, all characterized by a series of associated biological, geographical, and environmental data. The small mammals concerned are mainly rodents (10 species), shrews, and hedgehogs. The two invasive rodent species were the most numerous, exceeding in numbers all the other species pooled. This data set makes it possible to study coarse to fine‐scaled distribution of species of this commensal community in southern Senegal, as well as the possible determinants of this distribution in terms of habitat preferences and/or interspecific interactions. This data set can be freely used for non‐commercial purposes and is licensed under a Creative Commons Attribution 4.0 International License.

ddPCR increases detection of SARS-CoV-2 RNA in patients with low viral loads - Agnès Marchio; Christophe Batejat; Jessica Vanhomwegen; Maxence Feher; Quentin Grassin; Maxime Chazal; Olivia Raulin; Anne Farges-Berth; Florence Reibel; Vincent Estève; Anne Dejean; Nolwenn Jouvenet; et al. (Archives of Virology, 2021)
RT-qPCR detection of SARS-CoV-2 RNA still represents the method of reference to diagnose and monitor COVID-19. From the onset of the pandemic, however, doubts have been expressed concerning the sensitivity of this molecular diagnosis method. Droplet digital PCR (ddPCR) is a third-generation PCR technique that is particularly adapted to detecting low-abundance targets. We developed two-color ddPCR assays for the detection of four different regions of SARS-CoV-2 RNA, including non-structural (IP4-RdRP, helicase) and structural (E, N) protein-encoding sequences. We observed that N or E subgenomic RNAs are generally more abundant than IP4 and helicase RNA sequences in cells infected in vitro , suggesting that detection of the N gene, coding for the most abundant subgenomic RNA of SARS-CoV-2, increases the sensitivity of detection during the highly replicative phase of infection. We investigated 208 nasopharyngeal swabs sampled in March-April 2020 in different hospitals of Greater Paris. We found that 8.6% of informative samples (n = 16/185, P

Influence of infrastructure material composition and microtopography on marine biofilm growth and photobiology - Baptiste Vivier; Pascal Claquin; Christophe Lelong; Quentin Lesage; Mathias Peccate; Bastien Hamel; Marine Georges; Amel Bourguiba; Nassim Sebaibi; Mohamed Boutouil; Didier Goux; Jean-Claude Dauvin; et al. (Biofouling, 2021)

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

ReNovRisk: a multidisciplinary programme to study the cyclonic risks in the South-West Indian Ocean - Pierre Tulet; Bertrand Aunay; Guilhem Barruol; Christelle Barthe; Remi Belon; Soline Bielli; François Bonnardot; Olivier Bousquet; Jean-Pierre Cammas; Julien Cattiaux; Fabrice Chauvin; Idriss Fontaine; et al. (Natural Hazards, 2021)
Today, resilience in the face of cyclone risks has become a crucial issue for our societies. With climate change, the risk of strong cyclones occurring is expected to intensify significantly and to impact the way of life in many countries. To meet some of the associated challenges, the interdisciplinary ReNovRisk programme aims to study tropical cyclones and their impacts on the South-West Indian Ocean basin. This article is a presentation of the ReNovRisk programme, which is divided into four areas: study of cyclonic hazards, study of erosion and solid transport processes, study of water transfer and swell impacts on the coast, and studies of socio-economic impacts. The first transdisciplinary results of the programme are presented together with the database, which will be open access from mid-2021.

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Longitudinal predictors of bronchial hyperresponsiveness and FEV1 decline in bakers - Valérie Demange; Michel Grzebyk; Michel Héry; Nicole Massin; Christophe Paris; Pascal Wild (International Archives of Occupational and Environmental Health, 2021)

Population genomics in the arboviral vector Aedes aegypti reveals the genomic architecture and evolution of endogenous viral elements - Cristina M. Crava; Finny S. Varghese; Elisa Pischedda; Rebecca Halbach; Umberto Palatini; Michele Marconcini; Leila Gasmi; Seth Redmond; Yaw Afrane; Diego Ayala; Christophe Paupy; Rebeca Carballar‐Lejarazu; et al. (Molecular Ecology, 2021)
Horizontal gene transfer from viruses to eukaryotic cells is a pervasive phenomenon. Somatic viral integrations are linked to persistent viral infection whereas integrations into germline cells are maintained in host genomes by vertical transmission and may be co‐opted for host functions. In the arboviral vector Aedes aegypti , an endogenous viral element from a nonretroviral RNA virus (nrEVE) was shown to produce PIWI‐interacting RNAs (piRNAs) to limit infection with a cognate virus. Thus, nrEVEs may constitute a heritable, sequence‐specific mechanism for antiviral immunity, analogous to piRNA‐mediated silencing of transposable elements. Here, we combine population genomics and evolutionary approaches to analyse the genomic architecture of nrEVEs in A. aegypti . We conducted a genome‐wide screen for adaptive nrEVEs and searched for novel population‐specific nrEVEs in the genomes of 80 individual wild‐caught mosquitoes from five geographical populations. We show a dynamic landscape of nrEVEs in mosquito genomes and identified five novel nrEVEs derived from two currently circulating viruses, providing evidence of the environmental‐dependent modification of a piRNA cluster. Overall, our results show that virus endogenization events are complex with only a few nrEVEs contributing to adaptive evolution in A. aegypti .

Factors affecting adult body condition in the endangered northern rockhopper penguin - Karine Delord; Cédric Cotté; Pascal Terray; Charles-André Bost; Henri Weimerskirch; Christophe Barbraud (Marine Biology, 2021)

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Movements of three alcid species breeding sympatrically in Saint Pierre and Miquelon, northwestern Atlantic Ocean - Karine Delord; Christophe Barbraud; David Pinaud; Bruno Letournel; Baptiste Jaugeon; Herlé Goraguer; Pascal Lazure; Hervé Lormée (Journal of Ornithology, 2020)

Coastal Ocean and Nearshore Observation: A French Case Study - Lucie Cocquempot; Christophe Delacourt; Jérôme Paillet; Philippe Riou; Jérôme Aucan; Bruno Castelle; Guillaume Charria; Joachim Claudet; Pascal Conan; Laurent Coppola; Régis Hocdé; Serge Planes; et al. (Frontiers in Marine Science, 2019)

The Chemical Likelihood of Ribonucleotide-α-Amino acid Copolymers as Players for Early Stages of Evolution - Ziwei Liu; Ghinwa Ajram; Jean-Christophe Rossi; Robert Pascal (Journal of Molecular Evolution, 2019)

Long-term ecological observatories needed to understand ecohydrological systems in the Anthropocene: a catchment-scale case study in Brittany, France - Zahra Thomas; Pauline Rousseau-Gueutin; Benjamin W. Abbott; Tamara Kolbe; Hugo Le Lay; Jean Marçais; François Rouault; Christophe Petton; Pascal Pichelin; Geneviève Le Hennaff; Hervé Squividant; Thierry Labasque; et al. (Regional Environmental Change, 2019)

Three-dimensional flow characterization in a joint with plumose pattern - Benoit Nigon; Andreas Englert; Christophe Pascal (Hydrogeology Journal, 2019)

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Water content of limestones submitted to realistic wet deposition: a CIME2 chamber simulation - Anne Chabas; Jean-Pierre Sizun; Lucile Gentaz; Pauline Uring; Alain Phan; Adriana Coman; Stéphane Christophe Alfaro; Mandana Saheb; Edouard Pangui; Pascal Zapf; Florian Huet (Environmental Science and Pollution Research, 2018)

Early discontinuation of empirical antibacterial therapy in febrile neutropenia: the ANTIBIOSTOP study - Lenaïg Le Clech; Jean-Philippe Talarmin; Marie-Anne Couturier; Jean-Christophe Ianotto; Christophe Nicol; Ronan Le Calloch; Stéphanie Dos Santos; Pascal Hutin; Didier Tandé; Virginie Cogulet; Christian Berthou; Gaëlle Guillerm (Infectious Diseases, 2018)

Cooling history of nested plutons from the Variscan Tichka plutonic complex (Morocco) - Christophe Lécuyer; Dominique Gasquet; Pascal Allemand; François Martineau; Isabelle Martinez (International Journal of Earth Sciences, 2017)

Maximal tachycardia and high cardiac strain during night shifts of emergency physicians - Frédéric Dutheil; Fouad Marhar; Gil Boudet; Christophe Perrier; Geraldine Naughton; Alain Chamoux; Pascal Huguet; Martial Mermillod; Foued Saâdaoui; Farès Moustafa; Jeannot Schmidt (International Archives of Occupational and Environmental Health, 2017)

Mapping of new resistance (Vr2, Rm1) and ornamental (Di2, pl) Mendelian trait loci in peach - Thierry Pascal; Romain Aberlenc; Carole Confolent; Mathilde Hoerter; Elodie Lecerf; Christophe Tuéro; Patrick Lambert (Euphytica, 2017)

RGTA® or ReGeneraTing Agents mimic heparan sulfate in regenerative medicine: from concept to curing patients - Denis Barritault; Marie Gilbert-Sirieix; Kim Lee Rice; Fernando Siñeriz; Dulce Papy-Garcia; Christophe Baudouin; Pascal Desgranges; Gilbert Zakine; Jean-Louis Saffar; Johan van Neck (Glycoconjugate Journal, 2017)

Relating fitness to long‐term environmental variations in natura - Pascal Milesi; Thomas Lenormand; Christophe Lagneau; Mylène Weill; Pierrick Labbé (Molecular Ecology, 2016)
Quantifying links between ecological processes and adaptation dynamics in natura remains a crucial challenge. Many studies have documented the strength, form and direction of selection, and its variations in space and time, but only a few managed to link these variations to their proximal causes. This step is, however, crucial, if we are to understand how the variation in selective pressure affects adaptive allele dynamics in natural settings. We used data from a long‐term survey (about 30 years) monitoring the adaptation to insecticides of Culex pipiens mosquitoes in Montpellier area (France), focusing on three resistance alleles of the Ester locus. We used a population genetics model taking temporal and spatial variations in selective pressure into account, to assess the quantitative relationships between variations in the proximal agent of selection (amounts of insecticide sprayed) and the fitness of resistance alleles. The response to variations in selective pressure was fast, and the alleles displayed different fitness‐to‐environment relationships: the analyses revealed that even slight changes in insecticide doses could induce changes in the strength and direction of selection, thus changing the fitness ranking of the adaptive alleles. They also revealed that selective pressures other than the insecticides used for mosquito control affected the resistance allele dynamics. These fitness‐to‐environment relationships, fast responses and continuous evolution limit our ability to predict the outcome of adaptive allele dynamics in a changing environment, but they clearly contribute to the maintenance of polymorphism in natural populations. Our study also emphasizes the necessity of long‐term surveys in evolutionary ecology.

Oligomerized backbone pilin helps piliated Lactococcus lactis to withstand shear flow - Mickaël Castelain; Marie-Pierre Duviau; Virginie Oxaran; Philippe Schmitz; Muriel Cocaign-Bousquet; Pascal Loubière; Jean-Christophe Piard; Muriel Mercier-Bonin (Biofouling, 2016)

Control of shortwave radiation parameterization on tropical climate SST-forced simulation - Julien Crétat; Sébastien Masson; Sarah Berthet; Guillaume Samson; Pascal Terray; Jimy Dudhia; Françoise Pinsard; Christophe Hourdin (Climate Dynamics, 2016)

Jacques-Marie Bardintzeff: Tout savoir sur les volcans du monde, séismes et tsunamis - Eric Christophe Pascal Breard (Bulletin of Volcanology, 2016)

Characterization of endophytic Bacillus strains from tomato plants (Lycopersicon esculentum) displaying antifungal activity against Botrytis cinerea Pers - Asma Kefi; Imen Ben Slimene; Ines Karkouch; Christophe Rihouey; Sana Azaeiz; Marwa Bejaoui; Rania Belaid; Pascal Cosette; Thierry Jouenne; Ferid Limam (World Journal of Microbiology and Biotechnology, 2015)

p2 of Rice grassy stunt virus (RGSV) and p6 and p9 of Rice ragged stunt virus (RRSV) isolates from Vietnam exert suppressor activity on the RNA silencing pathway - Thanh Duc Nguyen; Séverine Lacombe; Martine Bangratz; Hoang Anh Ta; Do Nang Vinh; Pascal Gantet; Christophe Brugidou (Virus Genes, 2015)

From sewer inspection programmes to rehabilitation needs: research and results related to data quality and availability with the support of numerical experiment - Mehdi Ahmadi; Frédéric Cherqui; Jean-Christophe De Massiac; Pascal Le Gauffre (European Journal of Environmental and Civil Engineering, 2014)

Leaf‐associated fungal diversity in acidified streams: insights from combining traditional and molecular approaches - Hugues Clivot; Julien Cornut; Eric Chauvet; Arnaud Elger; Pascal Poupin; François Guérold; Christophe Pagnout (Environmental Microbiology, 2014)
Summary We combined microscopic and molecular methods to investigate fungal assemblages on alder leaf litter exposed in the benthic and hyporheic zones of five streams across a gradient of increasing acidification for 4 weeks. The results showed that acidification and elevated A l concentrations strongly depressed sporulating aquatic hyphomycetes diversity in both zones of streams, while fungal diversity assessed by denaturing gradient gel electrophoresis (DGGE) appeared unaffected. Clone library analyses revealed that fungal communities on leaves were dominated by members of Ascomycetes and to a lesser extent by Basidiomycetes and Chytridiomycetes. An important contribution of terrestrial fungi was observed in both zones of the most acidified stream and in the hyporheic zone of the reference circumneutral stream. The highest leaf breakdown rate was observed in the circumneutral stream and occurred in the presence of both the highest diversity of sporulating aquatic hyphomycetes and the highest contribution to clone libraries of sequences affiliated with aquatic hyphomycetes. Both methods underline the major role played by aquatic hyphomycetes in leaf decomposition process. Our findings also bring out new highlights on the identity of leaf‐associated fungal communities and their responses to anthropogenic alteration of running water ecosystems.

Invasive Geotrichum clavatum Fungal Infection in an Acute Myeloid Leukaemia Patient: A Case Report and Review - Vincent Camus; Marie-Laure Thibault; Marion David; Gilles Gargala; Patricia Compagnon; Fabien Lamoureux; Christophe Girault; Jean-Baptiste Michot; Aspasia Stamatoullas; Hélène Lanic; Fabrice Jardin; Pascal Lenain; et al. (Mycopathologia, 2014)

Analysis of Radionuclide Releases from the Fukushima Dai-ichi Nuclear Power Plant Accident Part II - Pascal Achim; Marguerite Monfort; Gilbert Le Petit; Philippe Gross; Guilhem Douysset; Thomas Taffary; Xavier Blanchard; Christophe Moulin (Pure and Applied Geophysics, 2014)

Thermal niches are more conserved at cold than warm limits in arctic‐alpine plant species - Loïc Pellissier; Kari Anne Bråthen; Pascal Vittoz; Nigel G. Yoccoz; Anne Dubuis; Eliane S. Meier; Niklaus E. Zimmermann; Christophe F. Randin; Wilfried Thuiller; Luc Garraud; Jérémie Van Es; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Understanding the stability of realized niches is crucial for predicting the responses of species to climate change. One approach is to evaluate the niche differences of populations of the same species that occupy regions that are geographically disconnected. Here, we assess niche conservatism along thermal gradients for 26 plant species with a disjunct distribution between the A lps and the A rctic. Location E uropean A lps and N orwegian F innmark. Methods We collected a comprehensive dataset of 26 arctic‐alpine plant occurrences in two regions. We assessed niche conservatism through a multispecies comparison and analysed species rankings at cold and warm thermal limits along two distinct gradients corresponding to (1) air temperatures at 2 m above ground level and (2) elevation distances to the tree line ( TLD ) for the two regions. We assessed whether observed relationships were close to those predicted under thermal limit conservatism. Results We found a weak similarity in species ranking at the warm thermal limits. The range of warm thermal limits for the 26 species was much larger in the Alps than in Finnmark. We found a stronger similarity in species ranking and correspondence at the cold thermal limit along the gradients of 2‐m temperature and TLD . Yet along the 2‐m temperature gradient the cold thermal limits of species in the Alps were lower on average than those in Finnmark. Main conclusion We found low conservatism of the warm thermal limits but a stronger conservatism of the cold thermal limits. We suggest that biotic interactions at the warm thermal limit are likely to modulate species responses more strongly than at the cold limit. The differing biotic context between the two regions is probably responsible for the observed differences in realized niches.

AUGC – IBPSA – 2012 - Christophe Petit; Pascal Perrotin (European Journal of Environmental and Civil Engineering, 2013)

A simple indicator to rapidly assess the short-term impact of heat waves on mortality within the French heat warning system - Annamaria Antics; Mathilde Pascal; Karine Laaidi; Vérène Wagner; Magali Corso; Christophe Declercq; Pascal Beaudeau (International Journal of Biometeorology, 2013)

The accuracy of plant assemblage prediction from species distribution models varies along environmental gradients - Julien Pottier; Anne Dubuis; Loïc Pellissier; Luigi Maiorano; Leila Rossier; Christophe F. Randin; Pascal Vittoz; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Climatic niche modelling of species and community distributions implicitly assumes strong and constant climatic determinism across geographical space. We tested this assumption by assessing how stacked‐species distribution models ( S ‐ SDMs ) perform for predicting plant species assemblages along elevation gradients. Location The western S wiss A lps. Methods Using robust presence–absence data, we first assessed the ability of topo‐climatic S ‐ SDMs to predict plant assemblages in a study area encompassing a 2800‐m wide elevation gradient. We then assessed the relationships among several evaluation metrics and trait‐based tests of community assembly rules. Results The standard errors of individual SDMs decreased significantly towards higher elevations. Overall, the S ‐ SDM overpredicted far more than they underpredicted richness and could not reproduce the humpback curve along elevation. Overprediction was greater at low and mid‐range elevations in absolute values but greater at high elevations when standardized by the actual richness. Looking at species composition, overall prediction success, kappa and specificity increased with increasing elevation, while the Jaccard index and sensitivity decreased. The best overall evaluation – as driven by specificity – occurred at high elevation where species assemblages were shown to be subject to significant environmental filtering of small plants. In contrast, the decreased overall accuracy in the lowlands was associated with functional patterns representing any type of assembly rule (environmental filtering, limiting similarity or null assembly). Main conclusions We provide a thorough evaluation of S ‐ SDM emphasizing the need to carefully interpret standard evaluation metrics, which reflect different aspects of assemblage predictions. We further reported interesting patterns of change in S ‐ SDM errors with changes in assembly rules along elevation. Yet, significant levels of assemblage prediction errors occurred throughout the gradient, calling for further improvement of SDMs , e.g. by adding key environmental filters that act at fine scales and developing approaches to account for variations in the influence of predictors along environmental gradients.

Nitrogen availability impacts oilseed rape (Brassica napus L.) plant water status and proline production efficiency under water-limited conditions - Benjamin Albert; Françoise Le Cahérec; Marie-Françoise Niogret; Pascal Faes; Jean-Christophe Avice; Laurent Leport; Alain Bouchereau (Planta, 2012)

Family history of malignant and benign thyroid diseases and risk of thyroid cancer: a population-based case–control study in New Caledonia - Christophe Leux; Thérèse Truong; Claire Petit; Dominique Baron-Dubourdieu; Pascal Guénel (Cancer Causes & Control, 2012)

The role of immigration and in‐situ radiation in explaining blood parasite assemblages in an island bird clade - JOSSELIN CORNUAULT; ANAÏS BATAILLARD; BEN H. WARREN; AMÉLIE LOOTVOET; PASCAL MIRLEAU; THOMAS DUVAL; BORJA MILÁ; CHRISTOPHE THÉBAUD; PHILIPP HEEB (Molecular Ecology, 2012)
Parasite communities on islands are assembled through multiple immigrations and/or in‐situ diversification. In this study, we used a phylogenetic approach to investigate the role of such processes in shaping current patterns of diversity in Leucocytozoon , a group of haemosporidian blood parasites infecting whites eyes ( Zosterops ) endemic to the Mascarene archipelago (south‐western Indian Ocean). We found that this parasite community arose through a combination of multiple immigrations and in‐situ diversification, highlighting the importance of both processes in explaining island diversity. Specifically, two highly diverse parasite clades appear to have been present in the Mascarenes for most of their evolutionary history and have diversified within the archipelago, while another lineage apparently immigrated more recently, probably with human‐introduced birds. Interestingly, the evolutionary histories of one clade of parasites and Indian Ocean Zosterops seem tightly associated with a significant signal for phylogenetic congruence, suggesting that host–parasite co‐divergence may have occurred in this system.

Modeling of CO2 Leakage up Through an Abandoned Well from Deep Saline Aquifer to Shallow Fresh Groundwaters - Pauline Humez; Pascal Audigane; Julie Lions; Christophe Chiaberge; Gaël Bellenfant (Transport in Porous Media, 2011)

A GIS-Based Multicriteria Evaluation for Aiding Risk Management Pinus pinaster Ait. Forests: A Case Study in Corsican Island, Western Mediterranean Region - Vanina Pasqualini; Pascal Oberti; Stéphanie Vigetta; Olivier Riffard; Christophe Panaïotis; Magali Cannac; Lila Ferrat (Environmental Management, 2011)

Evolution of the Sedrun landslide (Graubünden, Switzerland) with ortho-rectified air images - Johan Kasperski; Christophe Delacourt; Pascal Allemand; Pierre Pothérat (Bulletin of Engineering Geology and the Environment, 2010)

Prey capture attempts can be detected in Steller sea lions and other marine predators using accelerometers - Morgane Viviant; Andrew W. Trites; David A. S. Rosen; Pascal Monestiez; Christophe Guinet (Polar Biology, 2010)

The mariner Mos1 transposase produced in tobacco is active in vitro - Xavier Thomas; Sabah Hedhili; Laurent Beuf; Marie-Véronique Demattéi; Hélène Laparra; Giang Ngan Khong; Jean-Christophe Breitler; Frédéric Montandon; Elodie Carnus; Frédéric Norre; Daniel Burtin; Pascal Gantet; et al. (Genetica, 2010)

Proliferating cell nuclear antigen in gonad and associated storage tissue of the Pacific oyster Crassostrea gigas: seasonal immunodetection and expression in laser microdissected tissues - Alban Franco; Aude Jouaux; Michel Mathieu; Pascal Sourdaine; Christophe Lelong; Kristell Kellner; Clothilde Heude Berthelin (Cell and Tissue Research, 2010)

Are amphipod invaders a threat to regional biodiversity? - Christophe Piscart; Benjamin Bergerot; Pascal Laffaille; Pierre Marmonier (Biological Invasions, 2010)

Harmonin-b, an actin-binding scaffold protein, is involved in the adaptation of mechanoelectrical transduction by sensory hair cells - Nicolas Michalski; Vincent Michel; Elisa Caberlotto; Gaelle M. Lefèvre; Alexander F. J. van Aken; Jean-Yves Tinevez; Emilie Bizard; Christophe Houbron; Dominique Weil; Jean-Pierre Hardelin; Guy P. Richardson; Corné J. Kros; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Importance of abiotic stress as a range‐limit determinant for European plants: insights from species responses to climatic gradients - Signe Normand; Urs A. Treier; Christophe Randin; Pascal Vittoz; Antoine Guisan; Jens‐Christian Svenning (Global Ecology and Biogeography, 2009)
Aim We examined whether species occurrences are primarily limited by physiological tolerance in the abiotically more stressful end of climatic gradients (the asymmetric abiotic stress limitation (AASL) hypothesis) and the geographical predictions of this hypothesis: abiotic stress mainly determines upper‐latitudinal and upper‐altitudinal species range limits, and the importance of abiotic stress for these range limits increases the further northwards and upwards a species occurs. Location Europe and the Swiss Alps. Methods The AASL hypothesis predicts that species have skewed responses to climatic gradients, with a steep decline towards the more stressful conditions. Based on presence–absence data we examined the shape of plant species responses (measured as probability of occurrence) along three climatic gradients across latitudes in Europe (1577 species) and altitudes in the Swiss Alps (284 species) using Huisman–Olff–Fresco, generalized linear and generalized additive models. Results We found that almost half of the species from Europe and one‐third from the Swiss Alps showed responses consistent with the predictions of the AASL hypothesis. Cold temperatures and a short growing season seemed to determine the upper‐latitudinal and upper‐altitudinal range limits of up to one‐third of the species, while drought provided an important constraint at lower‐latitudinal range limits for up to one‐fifth of the species. We found a biome‐dependent influence of abiotic stress and no clear support for abiotic stress as a stronger upper range‐limit determinant for species with higher latitudinal and altitudinal distributions. However, the overall influence of climate as a range‐limit determinant increased with latitude. Main conclusions Our results support the AASL hypothesis for almost half of the studied species, and suggest that temperature‐related stress controls the upper‐latitudinal and upper‐altitudinal range limits of a large proportion of these species, while other factors including drought stress may be important at the lower range limits.

Climate change and plant distribution: local models predict high‐elevation persistence - CHRISTOPHE F. RANDIN; ROBIN ENGLER; SIGNE NORMAND; MASSIMILIANO ZAPPA; NIKLAUS E. ZIMMERMANN; PETER B. PEARMAN; PASCAL VITTOZ; WILFRIED THUILLER; ANTOINE GUISAN (Global Change Biology, 2009)
Mountain ecosystems will likely be affected by global warming during the 21st century, with substantial biodiversity loss predicted by species distribution models (SDMs). Depending on the geographic extent, elevation range, and spatial resolution of data used in making these models, different rates of habitat loss have been predicted, with associated risk of species extinction. Few coordinated across‐scale comparisons have been made using data of different resolutions and geographic extents. Here, we assess whether climate change‐induced habitat losses predicted at the European scale (10 × 10′ grid cells) are also predicted from local‐scale data and modeling (25 m × 25 m grid cells) in two regions of the Swiss Alps. We show that local‐scale models predict persistence of suitable habitats in up to 100% of species that were predicted by a European‐scale model to lose all their suitable habitats in the area. Proportion of habitat loss depends on climate change scenario and study area. We find good agreement between the mismatch in predictions between scales and the fine‐grain elevation range within 10 × 10′ cells. The greatest prediction discrepancy for alpine species occurs in the area with the largest nival zone. Our results suggest elevation range as the main driver for the observed prediction discrepancies. Local‐scale projections may better reflect the possibility for species to track their climatic requirement toward higher elevations.

Low impact of climate change on subalpine grasslands in the Swiss Northern Alps - PASCAL VITTOZ; CHRISTOPHE RANDIN; ANNELISE DUTOIT; FRANÇOIS BONNET; OTTO HEGG (Global Change Biology, 2009)
While phenological shifts and migration of isolated species under climate change have already been observed on alpine summits, very few studies have focused on community composition changes in subalpine grasslands. Here we use permanent plots monitored since 1954 and precisely located phytosociological censuses from 1970 to study compositional changes of subalpine grasslands in two distinct regions of the Swiss Northern Alps. In both areas, warming trends during the monitoring period were associated with changes in land management (abandonment of goat and sheep pasturing or grazing replaced by mowing). Old and recent inventories were compared with correspondence analyses (CA). Ecological indicator values, community‐affinities and biological traits of the species were used to infer the factors responsible for triggering the observed changes. In both regions, subalpine grasslands were stable with smaller changes than have previously been observed in alpine environments. Only a few species appeared or disappeared and changes were generally limited to increasing or decreasing frequency and cover of certain taxa. At one site, grazing abandonment favored fallow species. Some of these species were located at their upper altitudinal distribution limits and may have spread because of rising temperatures. In both areas, declining species were predominantly alpine and low‐growing species; their decline was probably due to increased competition (e.g., shadow) with more vigorous subalpine taxa no longer limited by grazing. We conclude that vegetation communities can respond rapidly to warming as long as colonization is facilitated by available space or structural change. In the subalpine grasslands studies, changes were mainly driven by land management. These communities have a dense vegetation cover and newly arriving herbaceous species preferring warmer conditions may take some time to establish themselves. However, climate disturbances, such as exceptional drought, may accelerate community changes by opening gaps for new species.

Prediction of plant species distributions across six millennia - Peter B. Pearman; Christophe F. Randin; Olivier Broennimann; Pascal Vittoz; Willem O. van der Knaap; Robin Engler; Gwenaelle Le Lay; Niklaus E. Zimmermann; Antoine Guisan (Ecology Letters, 2008)
The usefulness of species distribution models (SDMs) in predicting impacts of climate change on biodiversity is difficult to assess because changes in species ranges may take decades or centuries to occur. One alternative way to evaluate the predictive ability of SDMs across time is to compare their predictions with data on past species distributions. We use data on plant distributions, fossil pollen and current and mid‐Holocene climate to test the ability of SDMs to predict past climate‐change impacts. We find that species showing little change in the estimated position of their realized niche, with resulting good model performance, tend to be dominant competitors for light. Different mechanisms appear to be responsible for among‐species differences in model performance. Confidence in predictions of the impacts of climate change could be improved by selecting species with characteristics that suggest little change is expected in the relationships between species occurrence and climate patterns.

Internal variability in a regional climate model over West Africa - Emilie Vanvyve; Nicholas Hall; Christophe Messager; Stéphanie Leroux; Jean-Pascal van Ypersele (Climate Dynamics, 2008)

Predicting the Solubility of the Anti-Cancer Agent Docetaxel in Small Molecule Excipients using Computational Methods - Loan Huynh; Justin Grant; Jean-Christophe Leroux; Pascal Delmas; Christine Allen (Pharmaceutical Research, 2008)

Sodium valproate does not augment Prpsc in murine neuroblastoma cells - Christophe Legendre; Fabrice Casagrande; Thibault Andrieu; Domnique Dormont; Pascal Clayette (Neurotoxicity Research, 2007)

Water residence time: A regulatory factor of the DOM to POM transfer efficiency - Xavier Mari; Emma Rochelle-Newall; Jean-Pascal Torréton; Olivier Pringault; Aymeric Jouon; Christophe Migon (Limnology and Oceanography, 2007)
The pools of dissolved (DOM) and particulate organic matter (POM) and of transparent exopolymeric particles (TEP) were studied along two sampling gradients in the lagoon of New Caledonia in relation to the residence time of the water masses. The efficiency of the transfer of material from the dissolved to the particulate phase via TEP formation, indicating the physicochemical reactivity of organic matter, was investigated. DOM, POM, and TEP concentration increased along the sampling gradients, but their relative proportions varied. The contribution of the TEP pool to POM increased from 20% to 60%, from the most oligotrophic stations to the more anthropogenically affected bays. According to the low density of TEP and to the observed variations of the proportion of TEP compared with more conventional and solid particles, the aggregates formed inside the bays would be either neutrally or positively buoyant, whereas in the vicinity of the coral barrier, they would be negatively buoyant. As a result, the downward export of organic matter inside the bays might be greatly reduced, thereby prolonging the residence time of organic matter in the water column. The efficiency of the DOM/TEP transformation and the TEP turnover rate dropped drastically when the residence time increased from 0 to 50 d, suggesting that the reactivity of organic matter is reduced as it ages. The very high residence time of the water mass inside the bays, constrained by the hydrodynamic circulation inside the lagoon, favors the installation of a feedback system in which organic matter is not exported and is continuously degraded, leading to the formation of refractory DOM with a low physicochemical reactivity. In contrast, organic matter produced in areas in which water mass has a low residence time (i.e., near the coral barrier) is rapidly exported because of its high physicochemical reactivity.

A Complementary Method for Production of Tetraploid Crassostrea gigas Using Crosses Between Diploids and Tetraploids with Cytochalasin B Treatments - Helen McCombie; Christophe Ledu; Pascal Phelipot; Sylvie Lapègue; Pierre Boudry; André Gérard (Marine Biotechnology, 2005)

Novel Long-Circulating Lipid Nanocapsules - Didier Hoarau; Pascal Delmas; St#x00E9; phanie David; Emmanuelle Roux; Jean-Christophe Leroux (Pharmaceutical Research, 2004)

In situ-Forming Pharmaceutical Organogels Based on the Self-Assembly of L-Alanine Derivatives - Anne-Claude Couffin-Hoarau; Aude Motulsky; Pascal Delmas; Jean-Christophe Leroux (Pharmaceutical Research, 2004)

Differentiated thick ascending limb (TAL) cultured cells derived from SV40 transgenic mice express functional apical NHE2 isoform: effect of nitric oxide - Soline Bourgeois; Patrick Rossignol; Françoise Grelac; Cécile Chalumeau; Christophe Klein; Kamel Laghmani; Régine Chambrey; Patrick Bruneval; Jean-Paul Duong; Josiane Poggioli; Pascal Houillier; Michel Paillard; et al. (Pflügers Archiv - European Journal of Physiology, 2003)

Metabolic engineering of lactic acid bacteria for the production of nutraceuticals - Jeroen Hugenholtz; Wilbert Sybesma; Masja Nierop Groot; Wouter Wisselink; Victor Ladero; Kay Burgess; Douwe van Sinderen; Jean-Christophe Piard; Gerrit Eggink; Eddy J. Smid; Graciela Savoy; Fernando Sesma; et al. (Antonie van Leeuwenhoek, 2002)

Stress-induced premature senescence: from biomarkers to likeliness of in vivo occurrence - Olivier Toussaint; José Remacle; Jean-François Dierick; Thierry Pascal; Christophe Frippiat; Véronique Royer; Joao Pedro Magalhacs; Stéphanie Zdanov; Florence Chainiaux (Biogerontology, 2002)

Stress-induced premature senescence as alternativetoxicological method for testing the long-term effectsof molecules under development in the industry - Olivier Toussaint; Patrick Dumont; Jean-François Dierick; Thierry Pascal; Christophe Frippiat; Florence Chainiaux; Joao-Pedro Magalhaes; François Eliaers; José Remacle (Biogerontology, 2000)

ENVIRONMENTAL AUDITING: A Vegetation-Based Method for Ecological Diagnosis of Riverine Wetlands - Claude Amoros; Gudrun Bornette; Christophe Pascal Henry (Environmental Management, 2000)

Biological components from the Seine estuary: first results - Pascal Mouny; Jean Claude Dauvin; Christophe Bessineton; Bernard Elkaim; Serge Simon (Hydrobiologia, 1998)